1987
DOI: 10.1523/jneurosci.07-06-01626.1987
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythmicity restored by neural transplant. Immunocytochemical characterization of the graft and its integration with the host brain

Abstract: It is well established that overt circadian rhythms are permanently disrupted following lesions of the hamster hypothalamic suprachiasmatic nucleus (SCN). In the present study, we show that implantations of brain grafts containing the fetal SCN reestablish circadian rhythms of locomotor activity in adult hamsters previously made arrhythmic by SCN lesions. The restoration of free-running rhythms in conditions of constant darkness is correlated with the presence in the graft of neuropeptides normally present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
285
1
7

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 512 publications
(304 citation statements)
references
References 38 publications
(41 reference statements)
11
285
1
7
Order By: Relevance
“…Compelling evidence for a diffusible output signal derives from neural tissue transplantations in which the SCN from a fetal donor is implanted into the third ventricle of an adult, SCN-lesioned host. As mentioned previously, these grafts restore activity-related behaviors such as locomotor, drinking, and gnawing rhythms (Lehman et al, 1987;Ralph et al, 1990;Silver et al, 1990). That a diffusible signal is sufficient to restore locomotor rhythmicity in SCN-lesioned hosts was demonstrated by encapsulating donor SCN tissue in a membrane that prevented neural outgrowth while allowing the diffusion of signals between graft and host (Silver et al, 1996).…”
Section: Circadian Output and Orchestration Of Endocrine Function Difmentioning
confidence: 80%
See 1 more Smart Citation
“…Compelling evidence for a diffusible output signal derives from neural tissue transplantations in which the SCN from a fetal donor is implanted into the third ventricle of an adult, SCN-lesioned host. As mentioned previously, these grafts restore activity-related behaviors such as locomotor, drinking, and gnawing rhythms (Lehman et al, 1987;Ralph et al, 1990;Silver et al, 1990). That a diffusible signal is sufficient to restore locomotor rhythmicity in SCN-lesioned hosts was demonstrated by encapsulating donor SCN tissue in a membrane that prevented neural outgrowth while allowing the diffusion of signals between graft and host (Silver et al, 1996).…”
Section: Circadian Output and Orchestration Of Endocrine Function Difmentioning
confidence: 80%
“…The initial conclusion that the SCN serves as a brain master clock has been confirmed in the subsequent 30 years by converging lines of research involving in vivo, ex vivo, and in vitro studies carried out in many different laboratories. For example, transplants of donor SCN tissue into the brains of arrhythmic, SCN-lesioned hosts restore circadian rhythmicity in behavior (Lehman et al, 1987;Ralph et al, 1990). Importantly, rhythms are restored with the period of the donor SCN, indicating that the transplanted tissue does not act by restoring host brain function but that the "clock" is contained in the transplanted tissue.…”
Section: Identification Of a Brain "Clock": From Tissue To Genementioning
confidence: 99%
“…Neural transplantation has been a valuable approach to explore the potential for functional restoration after brain injury and damage (4,11) as well as to understand the normal functional organization of brain systems that mediate behavior and physiology (16). An example of the latter is in the field of circadian rhythms research, where transplantation has been used to investigate the signals and pathways by which the circadian clock communicates with the rest of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…The endogenous biological clock that controls mammalian circadian rhythms is located in the suprachiasmatic nuclei of the anterior hypothalamus and regulates a wide variety of circadian rhythms in behavior, autonomic function, and neuroendocrine physiology (27). Fetal grafts of the SCN restore robust behavioral rhythms to SCN-lesioned rats and hamsters (9,12,16), and cross-genotype grafting between clock mutant and wild-type animals has shown that restored rhythms are due to the presence of the donor pacemaker (21) The precise mechanisms by which SCN grafts restore function are still under investigation, but there is evidence for both neural efferents (18) and diffusible factors (24) as mediators of circadian clock function. In order to assess graft outgrowth and map the pattern of host innervation, markers must be used to identify the grafted tissue and its efferents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation